2006
DOI: 10.1124/jpet.106.103655
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Insulin-like Growth Factor-I Receptor Antisense Treatment Reduces Angiotensin Receptor Expression and Function in Spontaneously Hypertensive Rats

Abstract: The present study investigated the effects of a functional deficit in insulin-like growth factor-I signaling via chronic intravenous administration of insulin-like growth factor-I (IGF-I) receptor antisense in the conscious spontaneously hypertensive rat cardiovascular system. Insulin-like growth factor-I receptor (IGF-IR) antisense, but not full mismatch treatment, decreased IGF-IR expression in both conductance and resistance blood vessels. Aortic IGF-IR density was reduced by 67.4 Ϯ 6.0% in antisense-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…19) Furthermore, the involvement of IGF-I in regulation of arterial blood pressure is greater in SHR than in WKY. 20) Thus it is possible that activation of sensory neurons leading to an increase in IGF-I x mixed effects model (interaction between group and time) production plays a critical role in the normalization of systolic and diastolic BP in patients with hypertension. Serum levels of IGF-I in the hypertensive patients are significantly lower than those in the normotensive controls.…”
mentioning
confidence: 99%
“…19) Furthermore, the involvement of IGF-I in regulation of arterial blood pressure is greater in SHR than in WKY. 20) Thus it is possible that activation of sensory neurons leading to an increase in IGF-I x mixed effects model (interaction between group and time) production plays a critical role in the normalization of systolic and diastolic BP in patients with hypertension. Serum levels of IGF-I in the hypertensive patients are significantly lower than those in the normotensive controls.…”
mentioning
confidence: 99%
“…Moreover, malnourishment induces direct and/or indirect changes in neurohumoral systems that affect blood pressure regulation (Bell and Slotkin, 1988;Benabe et al, 1993a,b;Benabe and Martinez-Maldonado, 1993;Fernandez-Repollet et al, 1987;Ferreira et al, 2003;Hawkins et al, 2000;Langley-Evans et al, 1996a;Mi et al, 2000). Another important mechanism is related to the production of insulin growth factors (IGF): IGFs are produced under growth hormone (GH) stimulation of the hepatic cells (Conchillo et al, 2007) and are found to be vasodilator via NO production (Begum et al, 1998;Cruzado et al, 2005;Nguyen et al, 2006;Vickers et al, 2001). In malnourished animals, the production of GH may be impaired because of high levels of corticosterone (Langley-Evans et al, 1996a).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the studies showing that dominant negative or antisense oligonucleotides (ASO) of IGF-1R are able to attenuate neointima formation in an injured carotid artery rat model (Lim et al 2004) and reduce Ang II type 1 receptor (AT 1 R) expression and function in spontaneously hypertensive rats (Nguyen et al 2006) supports a potential pathogenic role of up-regulated IGF-1R signalling in vascular disease.…”
Section: Igf-1r Transactivation In Et-1-induced Signalingmentioning
confidence: 95%